2019
DOI: 10.21203/rs.2.18398/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of a nonsense mutation in TNNI3K associated with cardiac conduction disease and dilated cardiomyopathy

Abstract: Background Cardiac conduction disease(CCD) and dilated cardiomyopathy(DCM) are two common cardiovascular diseases which can lead to life-threatening conditions. The importance of heredity in these two diseases has been realized in recent years. Several casual genes have been found to be implicated in CCD and DCM such as LMNA,SCN5A,TTN,TNNI3K and so on. Rare genetic mutations in TNNI3K have been identified to be in connection with CCD and DCM.Methods Next generation sequencing(NGS) was carried out in order to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Resistance to stem rot (Sclerotinia sclerotiorum) Rapeseed [60] Resistance to Ascochyta blight and Fusarium wilt Chickpea [61] Resistance to black stem rust Durum wheat [31] Resistance to stripe rust Wheat [31] Resistance to blast, yellow mottle virus, bacterial leaf blight, and bacterial leaf stripe Rice [31] Resistance to Myrothecium leaf spot and yellow mosaic virus Soybean [31] Resistance to bacterial blight, cotton leaf curl virus Cotton [62] Phytophthora nicotiana var. parasitica Sesame [63] Resistance against pathogen striga (Striga asiatica) Maize [64] Table 3.…”
Section: Reaction Crop Referencesmentioning
confidence: 99%
“…Resistance to stem rot (Sclerotinia sclerotiorum) Rapeseed [60] Resistance to Ascochyta blight and Fusarium wilt Chickpea [61] Resistance to black stem rust Durum wheat [31] Resistance to stripe rust Wheat [31] Resistance to blast, yellow mottle virus, bacterial leaf blight, and bacterial leaf stripe Rice [31] Resistance to Myrothecium leaf spot and yellow mosaic virus Soybean [31] Resistance to bacterial blight, cotton leaf curl virus Cotton [62] Phytophthora nicotiana var. parasitica Sesame [63] Resistance against pathogen striga (Striga asiatica) Maize [64] Table 3.…”
Section: Reaction Crop Referencesmentioning
confidence: 99%
“…Previous studies have revealed that the Tnni3k locus on mouse chromosome 3 is related to cardiac survival, function, electrocardiographic PR‐interval 8,9 and viral myocarditis 10 . Human TNNI3K variants are related to cardiac disorders, including dilated cardiomyopathy, conduction disease and supraventricular arrhythmia 11–15 . Aberrant TNNI3K expression is observed in various cardiovascular diseases, such as myocardial hypertrophy, ischaemia/reperfusion injury and heart failure 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…10 Human TNNI3K variants are related to cardiac disorders, including dilated cardiomyopathy, conduction disease and supraventricular arrhythmia. [11][12][13][14][15] Aberrant TNNI3K ure. 16,17 Recent evidence has revealed that TNNI3K kinase activity is essential for maintaining normal cardiac physiology and that TNNI3K plays a crucial role in enhancing myocardial contractility.…”
mentioning
confidence: 99%